(untitled) (Al-Aasar, 2025)
Dr. Jaber Qameha was a distinguished Islamic thinker and writer who devoted his literary efforts to awakening the Muslim Ummah and guiding the contemporary Muslim to recognize the hidden plots and ideological attacks targeting Islam. His works aim to make Muslims aware of the political, cultural, and intellectual schemes designed to weaken their identity and values. Dr. Qameha’s writings focus on building a conscious Muslim who can face modern challenges with insight and faith. He authored several impactful books, such as The Impact of Missionary and Orientalist Movements on Muslim Youth, in which he warns against internal threats posed by Western-influenced Muslim elites. He distinguishes between fair-minded Orientalists who contributed to Islamic studies and biased ones who sought to distort Islam. In Enemies of Islam and Their Tools of Deception, he discusses various ideologies—like secularism, materialism, and Zionism—that work to undermine Islamic values. His book The Trial and Its Role in the Life of Muslims emphasizes that suffering is a divine test, echoing the experiences of past prophets and communities. Dr. Qameha also critiques the media’s role in distorting Arabic and Islamic culture in his book on media’s influence. He addresses Islamic governance and political participation in Opposition in Islam: Theory and Practice, advocating for balanced Islamic democracy. In Afghanistan’s Jihad Is Richer, he celebrates the Afghan resistance as a revival of Islamic dignity. He also honored Palestinian poet Abdul Rahim Mahmoud, seeing him as a symbol of literary and blood sacrifice. Through all his works, Dr. Qameha encourages Muslim youth to reconnect with Islamic history, uphold their values, and face contemporary challenges with intellect, courage, and unwavering belief in the mission of Islam۔